PENGARUH MOTIVASI USAHA DAN KOMITMEN USAHA TERHADAP KINERJA USAHA PADA UMKM MAKANAN RINGAN DI KECAMATAN TANAH SEREAL KOTA BOGOR - Farhan Julian Hamdani (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2025)
The purpose of this study was to analyze the responses of business owners to business motivation, business commitment and business performance and to determine the simultaneous and partial influence of business motivation and business commitment variables on business performance in snack food UMKM in Tanah Sereal District, Bogor City. The method used in this study is descriptive and verification. The sample size was 153 business owners using the purposive sampling method. Data collection techniques through observation, interviews, and distributing questionnaires to snack food UMKM business owners in Tanah Sereal District. The data analysis method uses a Likert scale for multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, f-test, and t-test. The test results conclude that simultaneously the variables of business motivation and business commitment have a positive and significant effect on business performance.